The influence of a single bout of swimming training on scapular upward rotation and muscle strength in junior club swimmers - Hatch, Graham (My University, 2015)
Swimming requires repetitive overhead movements that may lead to shoulder injury. Dysfunctions in the movements of the scapula have been associated with injury to overhead athletes in other sports. In addition, most of the current research describing scapular dysfunction in swimmers has assessed adults, with few studies assessing adolescent swimmers.